2014
DOI: 10.1177/147470491401200506
|View full text |Cite
|
Sign up to set email alerts
|

Life History Strategy and Young Adult Substance Use

Abstract: This study tested whether life history strategy (LHS) and its intergenerational transmission could explain young adult use of common psychoactive substances. We tested a sequential structural equation model using data from the National Longitudinal Survey of Youth. During young adulthood, fast LHS explained 61% of the variance in overall liability for substance use. Faster parent LHS predicted poorer health and lesser alcohol use, greater neuroticism and cigarette smoking, but did not predict fast LHS or overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(63 citation statements)
references
References 80 publications
(140 reference statements)
9
54
0
Order By: Relevance
“…Our results suggest that confounders fully subsumed any cross-round relationships between types of substance use and number of sexual partners across the span of early young adulthood. This is consistent with the literature we reviewed related to potential confounders in suggesting, for example, that substance use may function as a byproduct of mating effort or fast LHS (e.g., Richardson & Hardesty, 2012;Richardson et al, 2014). Richardson and Hardesty (2012) suggested that substance use might facilitate mating effort and consistent with this, we discussed various mechanisms that might explain such an effect (e.g., fitness indicator and/or other signaling functions, along with modulation of brain function).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our results suggest that confounders fully subsumed any cross-round relationships between types of substance use and number of sexual partners across the span of early young adulthood. This is consistent with the literature we reviewed related to potential confounders in suggesting, for example, that substance use may function as a byproduct of mating effort or fast LHS (e.g., Richardson & Hardesty, 2012;Richardson et al, 2014). Richardson and Hardesty (2012) suggested that substance use might facilitate mating effort and consistent with this, we discussed various mechanisms that might explain such an effect (e.g., fitness indicator and/or other signaling functions, along with modulation of brain function).…”
Section: Discussionsupporting
confidence: 73%
“…Extending upon prior work (Gerald & Higley, 2002;Vanyukov et al, 2012;Richardson et al, 2014), this study suggests that substance use should likely be understood as reflecting liability to a broad range of "risky" behaviors including multi-partner sex. Our findings imply that once we know participants" scores on confounders at each round in early young adulthood, information about their substance use seems to tell us little about their current prospects for A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 94%
See 1 more Smart Citation
“…Copping et al 2014;Gruijters and Fleuren 2018;Richardson et al 2017c). Research indicates, that K-factor has not subsumed mating effort and there are at least two separate dimensions of LHS: K-factor and mating effort (Richardson et al 2014(Richardson et al , 2017a; also see Copping et al 2014). There is a moderate negative residual correlation between them, which may be interpreted as a trade-off between the two LHS dimensions (Richardson et al 2017b).…”
Section: Psychometrics and Life History Strategiesmentioning
confidence: 99%
“…Although recent work criticizes the validity of applying LHT to trait variation within humans (e.g., Nettle and Frankenhuis, 2019;Zietsch and Sidari, 2019), this predictive lens has been useful for studying psychosocial developmental plasticity within underprivileged environments (see Kuzawa and Bragg, 2012). Relative to a slow life history strategy, people with faster life history strategies prefer immediate over delayed rewards (Griskevicius et al, 2011), reproduce earlier (Boothroyd et al, 2013;Hehman and Salmon, 2019), have more casual sex (Dunkel et al, 2015;Salmon et al, 2016), experience earlier sexual debut and report greater sexual risk-taking (James et al, 2012), pursue social status via dominance rather than prestige (Lukaszewski, 2015), score higher on measures of psychopathy (e.g., boldness, aggression, and disinhibition; Mededović, 2018) and dark personality (i.e., impulsivity, antisociality, entitlement/exploitativeness, Machiavellianism, and aggression;McDonald et al, 2012), and are more likely to use psychoactive substances (Richardson et al, 2014). These traits are advantageous in harsh, unpredictable environments to the extent that they help an individual to competitively capitalize on limited resources.…”
Section: Introductionmentioning
confidence: 99%